2007
DOI: 10.1021/jf0708490
|View full text |Cite
|
Sign up to set email alerts
|

Development and Agronomical Validation of New Fertilizer Compositions of High Bioavailability and Reduced Potential Nutrient Losses

Abstract: To optimize the economical cost of each unit of fertilizer applied and to reduce the environmental contamination caused by nutrient losses, the development of highly efficient granulated fertilizers is of great importance. This study proposes a strategy that consists of developing specific fertilizers having nutrient release patterns that are dependent on plant activity in the rhizosphere. This type of fertilizer is named "rhizosphere-controlled fertilizer" (RCF fertilizer). This fertilizer is based on the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 19 publications
1
44
1
6
Order By: Relevance
“…Obtained humic-metalphosphate complexes were only partially soluble in water but totally soluble in rhizospheric root exudates and neutral ammonium citrate (an indicator of potential P availability for plants) [47,49]. The main interest of compound fertilizers based on these types of complexes is that their potential soil fixation (P retrogradation) and leaching are very low due to their low water solubility, while they are able to provide available P for plants [46,47].…”
Section: The Fabrication Of Humic-mineral Complexes During the Manufamentioning
confidence: 99%
See 2 more Smart Citations
“…Obtained humic-metalphosphate complexes were only partially soluble in water but totally soluble in rhizospheric root exudates and neutral ammonium citrate (an indicator of potential P availability for plants) [47,49]. The main interest of compound fertilizers based on these types of complexes is that their potential soil fixation (P retrogradation) and leaching are very low due to their low water solubility, while they are able to provide available P for plants [46,47].…”
Section: The Fabrication Of Humic-mineral Complexes During the Manufamentioning
confidence: 99%
“…A number of studies have shown that the simultaneous reaction of phosphoric acid with alkaline compounds containing Mg (MgO products), and metals (for instance, Zn or Fe oxides or carbonates) in the presence of specific amounts of potassium or sodium salts of humic acids produced humic-double metal-phosphate complexes [47]. These complexes were identified in solid matrices using 31 P-NMR as described in Riggle and von Wandruska [42] and Erro et al [48].…”
Section: The Fabrication Of Humic-mineral Complexes During the Manufamentioning
confidence: 99%
See 1 more Smart Citation
“…Por ello, la aplicación de estos fertilizantes se realiza normalmente con dosis inferiores a aquellas de los fertilizantes hidrosolubles tradicionales. Por otra parte, los FLC pueden disminuir el impacto ambiental por lixiviación o volatilización de elementos nutritivos y, dada su relación costo-eficiencia, también son econó-micamente rentables en muchos cultivos (Erro, Urrutia, San Francisco, & García-Mina, 2007;Iyer, Dobrahner, Lowery, & Vandettey, 2002).…”
Section: Introductionunclassified
“…Therefore, the application of these fertilizers is normally at lower doses than those for traditional water-soluble fertilizers. Furthermore, the CRF can reduce leaching or volatilization of nutrients of environmental impact, and given their cost-effectiveness, they are also cost-effective in many crops (Erro, Urrutia, San Francisco & García-Mina, 2007;Lyer, Dobrahner, Lowery, & Vandettey, 2002). The CRF's use in Chile has been limited because the cost per unit item exceeds that of traditional soluble fertilizers.…”
Section: Introductionmentioning
confidence: 99%